Characterization and modeling of hardware imperfections in Schottky diode based six‐port modulator. Issue 6 (17th January 2019) - Pathak, Chetan; Rawat, Karun
Abstract: This article presents digital correction for hardware imperfection in mixer‐less six‐port modulator. A passive six‐port network correlates radio frequency carrier reflected from its different ports. If the reflection coefficients at these ports are controlled by in‐phase and quadrature‐phase baseband data, the modulated information is translated directly over the radio frequency carrier without any mixing action. However, the six‐port modulator has several hardware impairments resulting into linear and nonlinear distortion. This article presents a digital characterization and distortion mitigation scheme for six‐port modulator using new quadrature interference memory polynomial model and its variant. As a proof of concept, a prototype of digitally assisted six‐port modulator is designed to modulate QAM data to radio frequency carrier at 2.0 GHz. The measurement results show the capability of modulating 16 and 64 QAM data with very low EVM less than 1.2% after employing proposed digital correction scheme.